A Simple Model for the Integration of Goods and the Capital Market with Unionized Labor Markets - Buccella, Domenico (Ekonomika, 2019)
[full article and abstract in English]The present work analyzes the effects of goods and capital market integration on welfare. In an imperfectly competitive industry with unionized labor, openness to competition via exports, the possibility of holding minority stakes into a rival company and undertaking Greenfield Foreign Direct Investment (FDI) exemplify product and capital market liberalization, respectively. Challenging the “lieu commune” that liberalization a priori improves the social welfare of an economy, making use of a game-theoretic approach, it is shown that a domestic government should design the appropriate interventions in product and capital markets depending on the precise pattern of economic integration.
Keywords: market integration; cross-ownership; labor union; oligopoly; fixed wage; welfare